Comparative Prevalence of Ineffective Esophageal Motility: Impact of Chicago v4.0 vs. v3.0 Criteria - Teodora Surdea-Blaga; Stefan-Lucian Popa; Cristina Maria Sabo; Radu Alexandru Fărcaş; Liliana David; Abdulrahman Ismaiel; Dan Lucian Dumitrascu; Simona Grad; Daniel Corneliu Leucuta (Medicina)
Background and Objectives: The threshold for ineffective esophageal motility (IEM) diagnosis was changed in Chicago v4.0. Our aim was to determine IEM prevalence using the new criteria and the differences between patients with definite IEM versus “inconclusive diagnosis”. Materials and Methods: We retrospectively selected IEM and fragmented peristalsis (FP) patients from the high-resolution esophageal manometries (HREMs) database. Clinical, demographic data and manometric parameters were recorded. Results: Of 348 HREMs analyzed using Chicago v3.0, 12.3% of patients had IEM and 0.86% had FP. Using Chicago v4.0, 8.9% of patients had IEM (IEM-4 group). We compared them with the remaining 16 with an inconclusive diagnosis of IEM (borderline group). Dysphagia (77% vs. 44%, Z-test = 2.3, p = 0.02) and weight loss were more commonly observed in IEM-4 compared to the borderline group. The reflux symptoms were more prevalent in the borderline group (87.5% vs. 70.9%, p = 0.2). Type 2 or 3 esophagogastric junction morphology was more prevalent in the borderline group (81.2%) vs. 64.5% in IEM-4 (p = 0.23). Distal contractile integral (DCI) was lower in IEM-4 vs. the borderline group, and resting lower esophageal sphincter (LES) pressure and mean integrated relaxation pressure (IRP) were similar. The number of ineffective swallows and failed swallows was higher in IEM-4 compared to the borderline group. Conclusions: Using Chicago v4.0, less than 10% of patients had a definite diagnosis of IEM. The dominant symptom was dysphagia. Only DCI and the number of failed and inefficient swallows were different between definite IEM patients and borderline cases.